The Competence of School Principals: What Kind of Need Competence for School Success? - NFN Mustamin; M. Al Muz-zammil bin Yasin (Intelektual Pustaka Media Utama, 2012)
Competence is generally defined as the ability, the knowledge; attitudes and skills to do job effectively and efficiently. Because the school principals is a key success of a school, the this study can provide information about the competencies that need to be supplied to the school principals as educational leaders, who in accordance to various references, study results or documents. Hence, this study specifically focuses on the competence of school principals based on Ministry of Education Malaysia; Florida Department of Education, and Ministry of National Education Indonesia. Base on the purpose of this study, document analyzed was conducted by adapting methods of Concept Mapping. Based on the results obtained that, in generally competencies that need to be supplied to the competence of school principals based on schools; teachers (staff); and students. Meanwhile, results of document analyzed of the school principals from three documents are oriented to the school in general; oriented instructional leadership to the aspects of teaching done by teacher; and operational oriented to the school for student success. Therefore, this study suggests that the importance of school principals should be provided as has been highlighted competencies for school achievement.